Benthic habitat selection in juvenile European eel Anguilla anguilla: implications for coastal habitat management and restoration. Issue 5 (29th November 2018) - Christoffersen, Mads; Svendsen, Jon C.; Kuhn, Jesper A.; Nielsen, Anders; Martjanova, Anastasija; Støttrup, Josianne G.
Abstract : The critically endangered European eel Anguilla anguilla is dependent on suitable habitat qualities over a vast geographic area. Even though a significant proportion of the population never enters fresh water, the preferred benthic habitat is largely unknown in the marine environment. Examining substratum selection in A. anguilla reveals that elvers prefer coarse gravel, suggesting that conservation efforts may benefit from targeting this type of substratum in marine coastal areas.